Refractory Coeliac Disease: Diagnosis, Treatment, and Emerging Therapies - Agnieszka Starzyk; Piotr Charzewski (Quality in Sport)
Coeliac disease (CD) is a chronic immune-mediated disorder triggered by gluten ingestion in genetically predisposed individuals, leading to intestinal damage, malabsorption, and systemic complications. Although traditionally considered a gastrointestinal disorder, CD is now recognized as a multisystem condition with neurological, musculoskeletal, endocrine, and cardiovascular manifestations. Despite advancements in diagnostic tools, the disease remains underdiagnosed due to its diverse clinical presentations.